Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0262623
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia among geriatric trauma patients: A population-based study

Abstract: Objective To determine the significance of dysphagia on clinical outcomes of geriatric trauma patients. Methods This is a retrospective population-based study of geriatric trauma patients 65 years and older utilizing the Florida Agency for Health Care Administration dataset from 2010 to 2019. Patients with pre-admission dysphagia were excluded. Multivariable regression was used to create statistical adjustments. Primary outcomes included mortality and the development of dysphagia. Secondary outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Prescription medications associated with increased bleeding risk (antiplatelet agents and prescription nonsteroidal anti‐inflammatory drugs) and total count of prescribed medications were measured in the 90 days prior to cohort entry using Part D claims. Feeding tube placement and dysphagia were determined using claims definitions with 1‐year lookback 22,23 . Other markers of decline were ascertained using MDS data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prescription medications associated with increased bleeding risk (antiplatelet agents and prescription nonsteroidal anti‐inflammatory drugs) and total count of prescribed medications were measured in the 90 days prior to cohort entry using Part D claims. Feeding tube placement and dysphagia were determined using claims definitions with 1‐year lookback 22,23 . Other markers of decline were ascertained using MDS data.…”
Section: Methodsmentioning
confidence: 99%
“…Feeding tube placement and dysphagia were determined using claims definitions with 1-year lookback. 22,23 Other markers of decline were ascertained using MDS data. Data missingness was minimal.…”
Section: Covariatesmentioning
confidence: 99%
“…A study conducted in the US revealed that Parkinson's disease was diagnosed in over 50% of individuals age 85 and over (48), with 60% of Parkinson's patients experiencing pharyngeal dysphagia (7,47). In addition, other neurological disorders such as traumatic brain injury and neurological tumors can also affect the neural control of the pharynx, consequently impacting swallowing (49)(50)(51). Moreover, oral health issues such as tooth loss and dry mouth, cervical and laryngeal tumors, and postoperative esophageal stenosis can exacerbate dysphagia (52,53).…”
Section: Prevalence Of Dysphagia In An Aging Populationmentioning
confidence: 99%
“…Elderly patients reported higher rates of dysphagia than younger adults. The prevalence of dysphagia significantly increased over the past decades regarding the worldwide population aging [2 ▪▪ ,9]. Based on age, several comorbidities may be associated with a high prevalence of dysphagia, including dementia, Parkinson disease, head and neck cancer and stroke [2 ▪▪ ,10].…”
Section: Epidemiologymentioning
confidence: 99%